Fundamental aspects of the local approach to cutaneous ulcers - Colenci, Raquel [UNESP]; Fernandes Abbade, Luciana Patricia [UNESP] (Soc Brasileira Dermatologia, 2018)
Ulcers or wounds can be classified as acute or chronic. Their treatment involves overall assessment of the patient and choice of suitable local therapy, and the appropriate indication and use of products. Technological progress in the field of wound treatment has increased rapidly. Constant updating, with emphasis on available scientific evidence, is necessary to offer the best approaches to patients with acute and chronic wounds. A qualitative analysis of literature was conducted to identify scientific publications that update the concepts involved in local wound treatment, to present some resources that can aid the healing process and describe the different types of dressings available. This review includes wound assessment using the acronym TIME (tissue, infection/inflammation, moisture balance and edge of wound), cleaning and debridement, infection/inflammation control, exudate control, dressing types and main indications.
Keywords: Occlusive dressings; Wounds and injuries; Wound healing